2012
DOI: 10.4236/ajps.2012.37112
|View full text |Cite
|
Sign up to set email alerts
|

Improving Effect of Salicylic Acid on the Multipurpose Tree <i>Ziziphus spina-christi</i> (L.) Willd Tissue Culture

Abstract: Salicylic acid (SA) is one of numerous phenolic compounds found in plants with numerous important physiological events. Exogenously application of Salicylic acid (SA) is useful for the growth and development of plants. This investigation aimed to study the improving effect of salicylic acid on the tissue culture of Ziziphus spina-christi. To study its improving effect were used shoot-tip explants cultured on Murashige and Skoog (MS) solid medium supplemented with different concentrations and various combinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…Sakhanokho and Kelley (2009) who revealed that the positive effect of SA on plant tissue culture propagation may be a reflection of an increase in the meristematic number, where SA acts as morphoregulator signal to support the assumption that SA is a growth regulator. Our obtained results about the significant role of SA on calli match with those of Galal (2012) who confirmed that the exogenous addition of SA in culture media affected positively calli, shoot, and root propagation of Ziziphus spina-christi.…”
Section: Effect Of Phenyl Alanine or Salicylic Acid On Calli Growth Csupporting
confidence: 88%
“…Sakhanokho and Kelley (2009) who revealed that the positive effect of SA on plant tissue culture propagation may be a reflection of an increase in the meristematic number, where SA acts as morphoregulator signal to support the assumption that SA is a growth regulator. Our obtained results about the significant role of SA on calli match with those of Galal (2012) who confirmed that the exogenous addition of SA in culture media affected positively calli, shoot, and root propagation of Ziziphus spina-christi.…”
Section: Effect Of Phenyl Alanine or Salicylic Acid On Calli Growth Csupporting
confidence: 88%
“…A higher percentage of calli was induced by the addition of jasmonic acid to Vigna mungo tissue culture compared with the control (Mathews ). Salicylic acid is a phenolic compound found in plants that functions during plant growth, development, and photosynthesis (Raskin ) and, remarkably, positively affects plant callusing (Galal ). Together, these findings indicate that these DETs regulate the process of embryonic callus formation by responding to different hormone signals during cell enlargement, cell division, the suppression of cell differentiation, dedifferentiated cell maintenance and growth.…”
Section: Resultsmentioning
confidence: 99%
“…As a phenolic compound, Salicylic acid (SA) is found in plants, it has a role in a variety of physiological and biochemical processes. Exogenously applied SA is beneficial to plant growth and development [23,24]. Pyruvic acid is a junction molecule that gives energy to cells via the citric acid cycle (known as the Krebs cycle) when oxygen is present (aerobic respiration) and ferments to generate lactate (lactic acid) when oxygen is not available (anaerobic respiration) [25,26].…”
Section: Introductionmentioning
confidence: 99%